TESTING OF LOW SELF-CONTROL IN SOCIAL MEDIA USE OF GENERATION Z TOWARDS SOCIAL NETWORK IMPULSIVITY AND IMPULSIVE BUYING - Angelina Ananda Setiawan; Rully Arlan Tjahyadi (Jurnal Manajemen dan Bisnis Performa, 2025)
This study explains the relationships between low self-control, social network impulsivity, and impulse buying behavior within Generation Z by employing a causal-explanatory framework. The primary aim is to evaluate whether Generation Z possesses sufficient self-regulation to withstand the influences of social environments and the pervasive consumerist culture on social media, which often triggers impulsive purchasing decisions. Employing a purposive sampling strategy, the research targeted individuals aged 11 to 27 who actively engage with social media and have participated in online transactions. Data from 122 valid respondents were analyzed using validity and reliability assessments, classical assumption tests, and path analysis. The findings suggest that diminished self-control is linked to increased impulsivity in digital and broader social interactions, thereby contributing to impulse buying tendencies. These results have significant practical implications, highlighting the need to enhance awareness of self-regulation among Generation Z to mitigate impulsive shopping behaviors.